Family-centeredness in dementia care: what is the evidence?. (2nd January 2020) - Hao, Zhichao; Ruggiano, Nicole
ABSTRACT: Over the last decade, person-centered practices in care for adults with Alzheimer's disease and related dementias (AD/RD) has received significant attention from the health care and social service literature, though less attention has been paid to family-centered care (FCC). Initially conceptualized for application in pediatric care, FCC is an approach where clinicians develop partnerships with care recipients' family members and views family members as having expertise to contribute to the clinical team. More recently, FCC has been extended to the literature on AD/RD care, though little is known about the extent to which family-centered interventions have been developed for use in AD/RD clinical practice, or the effectiveness of family-centered care for this population. To contribute to gaps in scholarship, this systematic review identified and evaluated intervention studies examining FCC in AD/RD clinical care. Implications for research and practice are discussed.